Efforts to optimize thinking skills and acting through kit media in science learning in class vi sd 31 ambacang Kecamatan bayang - Surya Ningsih (Fakultas Sastra Universitas Ekasakti, 2018)
This research is based on the problems that arise in science learning, especially on basic matter or competence